Faktor-Faktor yang Mempengaruhi Partisipasi Petani dalam Kelompok Tani Hutan: Studi Kasus di KPH Way Terusan - Riyawan, I Nyoman; Wulandari, Christine (Universitas Pattimura, 2025)
This study examines the determinants influencing farmer participation in forest farmer groups (Kelompok Tani Hutan—KTH) within the jurisdiction of the Forest Management Unit (KPH) Way Terusan. Primary data were collected through structured surveys and in-depth interviews with 50 respondents, comprising both KTH members and non-members, during the period from August to September 2024. The study employs descriptive statistical analysis and Likert scale assessments to evaluate the socio-economic characteristics, institutional dynamics, and social factors that shape participation behavior. The findings reveal that the principal motivation for farmers to engage with KTH lies in securing legal access to forest resources through the Social Forestry Program, which fosters sustainable forest management practices and aims to enhance community livelihoods. Key factors affecting participation include perceived economic benefits, the effectiveness of institutional support provided by KPH Way Terusan, and the strength of social capital within local communities. However, despite these incentives, several critical barriers to effective participation remain, including limited market access for forest products, varying degrees of trust in KTH governance structures, and insufficient extension and capacity-building services. These results highlight the imperative to strengthen institutional frameworks and develop market-oriented support mechanisms to enhance the effectiveness of KTH in promoting sustainable forest management and improving socio-economic resilience among forest-dependent communities.